Dobro dziecka w pedagogiach zakonnych. Wybrane przykłady = Child`s welfare in pedagogy of religious congregations. Selected examples - Bartkowiak, Edyta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article examines the problem of "child`s welfare" in the education in theoretical and practical context in relation to religious congregation`s activities. Basing on traditions of the pedagogy of Order of the Holy Ghost and Congregation of the Sisters of Our Lady of Mercy, the role and impact of Church entities were showed. They implemented the idea of goodness in educational and care practices in reference to hardened and abandoned children.
Keywords: dobro dziecka; dobro; wartość; podmiotowość w edukacji; pedagogika zakonna; welfare; child`s welfare; values; subjectivity in education; religious pedagogy